Enhanced antitumor efficacy of STING agonist MSA-2 by lipid nanoparticles delivering circular IL-23 mRNA and platinum-modified MSA-2 combination - Tian He; Yating Li; Weiqi Li; Muqing Zhang; Guishuan Wang; Peng Zhou; Guoqi Song; Wenqing Li (Materials Today Bio)
A next-generation STING agonist MSA-2 is a promising tumor immunotherapy strategy. However, the methods for improving the anti-tumor efficacy of MSA-2 are a lot of effort. We have demonstrated antitumor effect of platinum-modified MSA-2 (MSA-2-Pt) was better than MSA-2. Here, we combined lipid nanoparticles delivering circular IL-23 mRNA (LNP@cIL-23) and MSA-2-Pt strategy, which showed good antitumor efficacy. Firstly, we synthesized a new series of ionizable phospholipids and formulated and optimized an LNP36 for delivering circular IL-23 mRNA. Then, the combination of LNP36@cIL-23 mRNA and MSA-2-Pt induced tumor cell death and immune activation in the tumor with a single i.t. injection. Finally, the combination of LNP36@cIL-23 mRNA and MSA-2-Pt significantly decreased the melanoma B16F10 tumor and prolonged the survival, demonstrating significant anti-tumor effects. This finding provides promising new avenues for STING activation strategies in tumor immunotherapy.